Peningkatan Kualitas Pelayanan Informasi Wisata Bukit Mahoni Melalui Optimalisasi Platform Bit.Ly sebagai Media Informasi Terintegrasi - Fatima Fatima; Aisyah Taskia; Annisa Ramadhani; Renata Renata; Mareva Rayhanah Putri; Arvita Rachmawaty; Sugeng Raharjo (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2026)
The development of digital media has significantly influenced the way tourism managers deliver information to the public. Social media is no longer used only as a means of communication, but also as a tool to support tourism promotion and information services so that they can be more easily accessed by potential visitors. Bukit Mahoni Tourism in Bangun Rejo Village has utilized several social media platforms as promotional media; however, the available information is still spread across various platforms, requiring visitors to open multiple applications to obtain the information they need. This condition makes access to information less practical and has not yet been supported by a digital user activity monitoring system. This community service activity aims to help improve the quality of tourism information services through the optimization of the Bit.ly platform as an integrated information medium. The activity was carried out using a participatory approach involving Pokdarwis Mentari as the tourism management group. The stages of the activity included field surveys, platform design and implementation, management assistance, as well as program monitoring and evaluation. The results showed that all tourism information was successfully integrated into a single digital link that is easier for visitors to access. During the monitoring period from February 17 to May 17, 2026, the digital information link recorded 301 views and 255 engagements, with an engagement rate of 84.7%. These findings indicate that the implemented information media was quite effective in helping visitors obtain tourism information more quickly and practically. In addition, tourism managers also became capable of independently managing digital information and utilizing simple analytical features to support more effective and sustainable digital-based tourism promotion activities.